Korelasi Jumlah Folikel Ovarium dengan Konsentrasi Hormon Estrogen Mencit (Mus musculus) setelah Konsumsi Harian Tepung Kedelai selama 40 Hari - Mardiati, Siti Muflichatun; Sitasiwi, Agung Janika (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2008)
Soybeans contains phytoestrogen that influence reproductive process. Phytoestrogen administration withchronical dosage along growth periode cause the neuroendocrine system disturbance. Commonly in humanintake of phytoestrogen from soybeans or other soybeans product. So it is important to research beneficialand adverse effects of soybeans consumption with chronical dosage to reproductive process, particulary iscorelation between the sum of ovarium follicles and the estrogen level of mouse (Mus musculus) after dailyconsumption of soybeans along 40 days. The objective of this study was to know the corelation betweenthe sum of ovarium follicle and the estrogen level of mouse, by experimental design. Adult female micewere use as experimental animal, divided into two groups, there were control and treatment. Thegroup of treatment was administrated with 0,975 mg soybeans flour, it was contain Â± 0,00156 mgphytoestrogen. The control group was administreted only drinking water. The result of this study showsthat were not significantly difference between control and treatment group. It concluded the corelationbetween the sum of ovarium follicles and the estrogen level were not influenced with daily consumption offitoestrogen.